BÄ«'ah Lughawiyah Programs in Arabic Language Learning to Improve Student's Arabic Speaking Skills - Setiyadi, Alif Cahya; Hidayah, Nurul; Wahyudi, Muhammad; Br Maha, Marheni (UIN Sunan Gunung Djati Bandung, 2023)
This research aims at describing the language program based on bÄ«'ah lughawiyah as an Arabic-language medium in improving the ability of Arabic speaking skills (mahÄrah kalÄm) undertaken by PUSDIKLAT UNIDA Gontor at the Pesantren Tahfizhul Qur'an SahabatQu, Deresan, Yogyakarta. The main research problem is related to the strategy undertaken by PUSDIKLAT UNIDA Gontor in developing the Arabic language environment. To answer this research question, the method used is descriptive qualitative. Research data sources are the Pesantren manager and students at the Pesantren Tahfizhul Qur'an SahabatQu, Deresan, Yogyakarta. The research used several data collection techniques, interviews, observation, and documentation. Data analysis techniques in qualitative research systematically track and organize field notes obtained from interviews, observations, and other materials so that researchers can report research results. The results showed that PUSDIKLAT UNIDA Gontor had done some strategies in developing the Arabic language environment. The activities of the bÄ«â€™ah lughawiyah including ilqÄ' al mufradÄts (giving Arabic vocabulary), musyÄhadah (watching), language games, Arabic speech, taqdÄ«m al qishah (Arabic drama), Arabic poetry, master of ceremony (MC) Arabic, and muhÄdatsah. These programs improved the speaking ability of most female students in the Pesantren Tahfizhul Qur'an SahabatQu, Deresan, Yogyakarta, precisely in utilizing Arabic as the daily communication medium and eliminating the rigidity of learners in expressing the contents of their minds.